The art and neurology of Paul Richer - Maranhão-Filho, Péricles (Arquivos de Neuro-Psiquiatria, 2017)
In the 1890s, one of Charcot’s most important protégés, Dr. Paul Richer (1849–1933), drew and sculpted a series of representations of the main types of nerve pathology. That series included drawings of pleomorphic hysterical crises and sculptures depicting patients suffering from labio-glosso-laryngeal paralysis and myopathy, as well as Parkinson’s disease. Richer was a resident at La Salpêtrière and, in 1882, became head of the Charcot museum. Early in his career, despite having no formal artistic training, he could represent masterfully, in drawings and sculptures, people’s tragic suffering from neurological diseases. Later on, with the same tools, he expressed the beauty of human movements in health.
Keywords: Paul Richer; drawings; sculpture; neurology; art